Effect of fear on dental utilization behaviors and oral health outcome - Meng X, Heft MW, Bradley MM, Lang PJ. (Blackwell Synergy, 2007)
This paper assesses the effect of fear on a number of dental utilization behaviors and oral heath outcome in a sample of adult Floridians.